Selling Vibes or Selling Product? The Role of Store Atmosphere on Consumer Loyallty - Sheren Yen Yen Hong; David P. E. Saerang; Emilia M. Gunawan (Universitas Sam Ratulangi, 2022)
The purpose of this research is to identify how is the store atmosphere affected the consumer loyalty. The sample size used for this research was 15 informants of Starbucks Manado that already reach gold level in their membership. . Increase persistence, Triangulation and using reference materials was applied to confirm the attributes of each statements and to assess the validity and reliability. The result shows that Store Atmosphere it does affected the consumer loyalty â€“ comprising 6 elements: Lighting, Music, Aroma, Temperature, Spatial Planning and Building design. It was found that Store atmosphere plays a significant role in Starbucks Manado consumer loyalty. However, the music is not all agreed because of personal preferences.Â